2011
DOI: 10.1007/s00421-011-2056-3
|View full text |Cite
|
Sign up to set email alerts
|

Fluid intake and changes in limb volumes in male ultra-marathoners: does fluid overload lead to peripheral oedema?

Abstract: An increase in body mass due to oedema has been previously described. The aim of this study was to investigate a potential association between both fluid and electrolyte intake and the formation of peripheral oedemas. Fluid and electrolyte intakes and the changes in limb volumes in 50 male 100-km ultra-marathoners were measured. Pre- and post-race serum sodium concentration ([Na(+)]), serum aldosterone concentration, serum copeptin concentration, serum and urine osmolality and body mass were determined. Fluid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
52
5

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(63 citation statements)
references
References 69 publications
(109 reference statements)
6
52
5
Order By: Relevance
“…Although this study lacks some data about factors of endurance performance such as physiological and anthropometric parameters, training characteristics, previous experience and fluid intake (Bracher et al 2011;Bürge et al 2011;Knechtle et al 2010a, b, c; and environmental conditions of the race (Ely et al 2007;Wegelin and Hoffman 2011;Vihma 2010), it provides valuable data because master runners present a unique model to study the effects of high levels of physical training into older age . The percent of both male and female 100-km finishers for the age groups comprised between 40 and 59 years increased during the 1998-2010 period.…”
Section: Resultsmentioning
confidence: 99%
“…Although this study lacks some data about factors of endurance performance such as physiological and anthropometric parameters, training characteristics, previous experience and fluid intake (Bracher et al 2011;Bürge et al 2011;Knechtle et al 2010a, b, c; and environmental conditions of the race (Ely et al 2007;Wegelin and Hoffman 2011;Vihma 2010), it provides valuable data because master runners present a unique model to study the effects of high levels of physical training into older age . The percent of both male and female 100-km finishers for the age groups comprised between 40 and 59 years increased during the 1998-2010 period.…”
Section: Resultsmentioning
confidence: 99%
“…It was shown that mutant mice that selectively lack S1P in plasma are characterized by increased basal and inflammation-induced vascular leak (Camerer et al, 2009). Peripheral edema is frequently observed in athletes completing an ultramarathon run (Bracher et al, 2012), and it is tempting to speculate that reduced plasma S1P level may contribute to this effect. As mentioned in the introduction, the main source of plasma S1P is erythrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies postulate rather fluid overload as the source of the swellings,31 32 and total body water increase has been shown33 in long endurance athletes. Fluid intake had been shown to be positively correlated with the change of the volume of athletes' feet34; furthermore, it has been shown that the total body water has increased over the course of multistage runs 35…”
Section: Discussionmentioning
confidence: 99%